Examination of Students’ Perceptions about Computer Lessons Carried out with Gamification - Ayhan Sarı, Taner Altun (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2016)
This study aimed to examine high school students’ views about effects of gamification on their interests, motivation towards and participation in to lessons. Case study designation within qualitative research approach was adopted in the study. The study was carried out in a Vocational and Technical Anatolian High School with 27 students who attend to Information Technologies Department at that school. “Number Systems” and “Logical Gate Circuits” topics were instructed by the teacher for 4 weeks and some gamification elements were included in the lessons. Formerly module was taught by using traditional teaching methods but this time some of the gamification elements such as based on students’ performances some materials (stars, badges, league tables etc.,) and electronic result graphs were shared with students both in the class and on the Internet vis social media. Within the process students’ actions in the class were observed and recorded through semi-structured observation forms. At the end of 4 weeks randomly selected 7 participated students were interviewed about the learning activities which included gamification. According to data analysis results it is found that gamification elements increases students’ interests and motivation towards computer lessons and makes them more active in terms of participating into lessons. At the end of the study some recommendations about effective use of gamification in lessons were made for researchers and teachers.